A TECHNICAL STUDY OF SOLAR AND BIOGAS ENERGY USAGE IN ELECTRIC VEHICLES IN ILHABELA, BRAZIL - Micena, Raul Pereira [UNESP]; Llerena P, Omar R. [UNESP]; Lamas, Wendell de Queiroz; Silveira, Jose Luz [UNESP] (Univ Politecnica Salesiana Ecuador-salesian Polytecnic Univ, 2018)
Currently, Hybrid Power Systems (HPS) have been shown as an excellent opportunity for generation of electricity. This paper presents the study of a hybrid system considering two energy sources (solar - biogas) available in the city Ilhabela island in the state of Sao Paulo - Brazil. This system will supply electricity to electric vehicles. The study is based on the calculation of the energy demand of the electric vehicles on the island. Then the capacity of biogas production in Ilhabela is determined. Subsequently, in order to know the energy produced and the amount of biogas needed by the microturbine, an energy analysis of this plant is carried out. Last, the energy needed to be generated with the photovoltaic plant is calculated. The results show that, considering a market insertion index of 4% of electric vehicles, the average energy demand is 46.327 kWh/month. On the other hand, the amount of biogas produced on the island is twice that needed to generate 16.200 kWh/month. Finally, the solar plant will produce 30.127 kWh/month.
Keywords: Biogas; Electric Vehicles; Solar Energy; Ilhabela